Exploring ESG challenges and opportunities : navigating towards a better future - Grima, Simon; Maditinos, Dimitrios; Noja, Gra̦iela-Georgiana; Stankevičienė, Jelena; Tarczynska-Luniewska, Malgorzata; Thalassinos, Eleftherios I. (Contemporary studies in economic and financial analysis ;, 2024)
The number of companies that are adopting sustainability strategies and disclosing information related to Environmental, Social and Corporate governance (ESG) issues is on the rise. This special volume encapsulates the transformative journey businesses undertake to balance profitability with responsibility. ESG is not merely a set of criteria; it is a compass guiding business toward a destination where financial success converges with societal and environmental well-being. Contemporary Studies in Economic and Financial Analysis publishes a series of current and relevant themed volumes within the fields of economics and finance. Both disciplinary and interdisciplinary studies are welcome.